Perilaku Konsumen Muslim Indonesia Terhadap Perkembangan Produk Makanan dan Minuman Halal - Burhanuddin Burhanuddin; Setyo Riyanto (STKIP PGRI SITUBONDO, 2022)
The manuscript aims to find out the impact of modernization on lifestyle in some Muslim communities who tend to pay less attention to religious parameters (Islam) in consuming food products, medicine, and even cosmetics. The research method used is antics research. The analysis results mention that anything consumed from an Islamic perspective has implications for mental health. Halal standardization has also been strengthened by the Law of the Republic of Indonesia Number 33 of 2014 concerning Halal Product Assurance as a whole to all walks of life. In addition, the Government has also formed a body called the Halal Product Assurance Organizing Agency (BPJPH), which is tasked with organizing Halal Product Guarantees (JPH). This shows that the Government is also very concerned about the needs of its citizens in meeting the consumption of all products with halal standards. The research method used is library research (library research), using data collection techniques through several theoretical and empirical literature